NMMHC IIA Inhibition Ameliorates Cerebral Ischemic/Reperfusion-Induced Neuronal Apoptosis Through Caspase-3/ROCK1/MLC Pathway - Wang GY; Wang TZ; Zhang YY; Li F; Yu BY; Kou JP (Dove Medical Press, 2020)
Guang-Yun Wang,1 Tie-Zheng Wang,1 Yuan-Yuan Zhang,1 Fang Li,1 Bo-Yang Yu,2 Jun-Ping Kou1 1State Key Laboratory of Natural Products, Jiangsu Key Laboratory of TCM Evaluation and Translational Research, Department of Pharmacology of Chinese Material Medica, School of Traditional Chinese Pharmacy, China Pharmaceutical University, Nanjing 211198, People’s Republic of China; 2State Key Laboratory of Natural Products, Jiangsu Key Laboratory of TCM Evaluation and Translational Research, Department of Resource and Development of Chinese Material Medica, School of Traditional Chinese Pharmacy, China Pharmaceutical University, Nanjing 211198, People’s Republic of ChinaCorrespondence: Jun-Ping KouState Key Laboratory of Natural Products, Jiangsu Key Laboratory of TCM Evaluation and Translational Research, Department of Pharmacology of Chinese Material Medica, School of Traditional Chinese Pharmacy, China Pharmaceutical University, Nanjing 211198, People’s Republic of ChinaEmail junpingkou@cpu.edu.cnPurpose: Our previous studies have indicated that non-muscle myosin heavy chain IIA (NMMHC IIA) is involved in H2O2-induced neuronal apoptosis, which is associated with the positive feedback loop of caspase-3/ROCK1/MLC pathway. However, the neuroprotective effect of NMMHC IIA inhibition with an adeno-associated virus (AAV) vector after transient middle cerebral artery occlusion (MCAO) and its role in caspases-3/ROCK1/MLC pathway remain blurred.Methods: Green fluorescent protein (GFP) and a small hairpin RNA targeting Myh9 (encoding NMMHC IIA) were cloned and packaged into the AAV9 vector. AAV-shMyh9 or control vector were injected into C57BL/6J mice four weeks prior to 60 min MCAO. Twenty-four hours after reperfusion, functional and histological analyses of the mice were performed.Results: In this study, AAV-shMyh9 was used to down-regulate NMMHC IIA expression in mice. We found that down-regulation of NMMHC IIA could improve neurological scores and histological injury in ischemic mice. Ischemic attack also activated neuronal apoptosis, and this effect was partially attenuated when NMMHC IIA was inhibited by AAV-shMyh9. In addition, AAV-shMyh9 significantly reduced cerebral ischemic/reperfusion (I/R)-induced NMMHC IIA-actin interaction, caspase-3 cleavage, Rho-associated kinase1 (ROCK1) activation and myosin light-chains (MLC) phosphorylation.Conclusion: Consequently, we showed that AAV-shMyh9 inhibits I/R-induced neuronal apoptosis linked with caspase-3/ROCK1/MLC/NMMHC IIA-actin cascade, which has also been confirmed to be a positive feedback loop. These findings put some insights into the neuroprotective effect of AAV-shMyh9 associated with the regulation of NMMHC IIA-related pathway under ischemic attack and provide a therapeutic strategy for ischemic stroke.Keywords: NMMHC IIA, adeno-associated virus, ischemic stroke, apoptosis